Identidades territoriais nas comunidades afrodescendentes urbanas: do cerrado de Goiás aos igarapés do Amapá - Santos, Fátima Sueli Oliveira dos (2019)
Traditional quilombola communities are not always recognized in urban territories, because the perception that citizens of the city have about quilombola territory, permeates a different location in relation to smell, structure and relational environment. In view of this conception, it was sought, through a study of quilombola urban territorial identities, to identify how these communities traditionally preserved their territorial identities, how they built their identities and at what time they resignified themselves. In order to obtain this understanding, we used the approach of cultural geography, historical geography, anthropology, sociology so that this knowledge would be expanded and not limited to geography, the human sciences have an interconnectedness of thought. In addition to these sciences, the scientific methods covered were phenomenology and dialectic, in order to understand the way of life of quilombola communities, their production in the territory, their cultural manifestations, even though they are in urban centers. As a methodological instrument, techniques used by the Participatory Rural Diagnosis were adapted, from which quantitative and qualitative participant observation research was used, with interviews and questionnaires, venn diagram, metal map, use of google maps, dronne, camera, meetings with the community and government agencies to present the final result of the study. Therefore, at the end of a research of this nature, it is necessary to perceive the identity multi-territoriality of traditional urban quilombola communities, since, by "bringing in from outside", there is an identity empowerment in which the identity phenomenon dialogues with the territory and articulates the multiple territorial identities in urban quilombos.